Corporate Fraud, Governance, and Auditing - Pagano, Marco; Immordino, Giovanni (The Review of Corporate Finance Studies, 2012)
We analyze corporate fraud in a setting in which managers have superior information but are biased against liquidation because of their private benefits from empire building. This may induce them to misreport information and even bribe auditors when liquidation would be value-increasing. To curb fraud, shareholders optimally design corporate governance by jointly choosing audit quality and managerial compensation. We analyze how country-level rules affect these firm-level choices. Our analysis underscores that different country-level governance provisions have different effects on firm-level governance: Some act as substitutes of internal governance mechanisms, whereas others enhance their effectiveness and therefore complement them. (JEL G28, K22, M42)